ANALYSIS OF FACTORS AFFECTING CRYPTOCURRENCY RETURN DURING THE COVID-19 PANDEMIC - Andriansyah, Andriansyah; Amalia Fachrudin, Khaira (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to analyze the effect of Asset Price, Transaction Volume and Market Capitalization on Cryptocurrency Return. This study uses secondary data in the form of a 2020 weekly report accessed at www.Indodax.com. The data analysis method in this study uses panel data regression analysis which is processed using eviews 10. The partial results show that asset price has a negative and insignificant effect on cryptocurrency returns, transaction volume has a positive and insignificant effect on cryptocurrency returns, market capitalization has a negative and negative effect and not significant to the return of cryptocurrencies. The results of the study simultaneously show that asset price, transaction volume and market capitalization have a negative and insignificant effect on the dependent variable, namely cryptocurrency returns with an R-squared value of 1.1682%. Suggestions for further research are to add other variables that affect cryptocurrency returns such as macroeconomics.